2020
DOI: 10.1519/jsc.0000000000002916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Core Stabilization Training Program on Performance of Ballet and Modern Dancers

Abstract: Kalaycioglu, T, Apostolopoulos, NC, Goldere, S, Duger, T, and Baltaci, G. Effect of a core stabilization training program on performance of ballet and modern dancers. J Strength Cond Res 34(4): 1166–1175, 2020—The aim of this study was to investigate the effects of a core stabilization training (CST) program on performance of university-level ballet and modern dancers. Twenty-four dancers between the ages of 18 and 24 years participated in the study. Core stabilization training was performed for 45–60 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…This is clearly demonstrated by the ability to combine strength and speed while performing the jump skill in question. In agreement with (Fuller et al, 2020;Ko et al, 2020;McGill et al, 2019b) In agreement with (Faria et al, 2013;Kalaycioglu et al, 2020;Phan et al, 2020; Result List: Ballet: Discovery Service for Saudia Digital Library, n.d.)…”
Section: /6 Statistical Treatmentsmentioning
confidence: 98%
“…This is clearly demonstrated by the ability to combine strength and speed while performing the jump skill in question. In agreement with (Fuller et al, 2020;Ko et al, 2020;McGill et al, 2019b) In agreement with (Faria et al, 2013;Kalaycioglu et al, 2020;Phan et al, 2020; Result List: Ballet: Discovery Service for Saudia Digital Library, n.d.)…”
Section: /6 Statistical Treatmentsmentioning
confidence: 98%
“…The use of iontophoresis and phonophoresis, Lower leg braces versus no braces , no significant differences for either lower leg braces was found and concluded that , after examination of all treatment extracorporeal shockwave therapy (ESWT) appears to be the most promising [37] . Core stabilisation training was performed after and before evaluation of physical fitness parameters included vertical jump performance, flexibility, dynamic balance, coordination, proprioception, muscle and hip flexion is isokinetic strength measure and concluded that improvement of joints reposition, and jump performance in universities level pre-professional dancers and after 8 weeks with core stabilisation exercises (CTS) program [38] .…”
Section: Kenny Et Al (2012)mentioning
confidence: 99%
“…The use of trunk training to develop the lumbopelvic-hip-complex or "core" has been identified as a very important component in general fitness, rehabilitation, and strength and conditioning (S&C) settings (3,6,11,20,23,30). Throughout the literature, core stability training has been cited as a potential method to help improve performance in both sporting activities and daily living among individuals (10,12,15,20,31,40,41). The term "core" refers to the musculature of the trunk region which has previously been divided into three categories: 1) global core stabilizers (e.g., erector spinae and rectus abdominus), 2) local core stabilizers (e.g., multifidus, transverse abdominus, and interspinalis), and 3) upper and lower extremity core-limb transfer muscles (e.g., latissimus dorsi, psoas, and gluteals) (23,39).…”
Section: Introductionmentioning
confidence: 99%
“…From a sporting context, "core stability" has been defined as "the ability to control the position and motion of the trunk over the pelvis to allow optimum production, transfer, and control of force and motion to the terminal segment in integrated athletic activities" (15,16). The importance of this lumbopelvic stability, especially in athletic events, is highlighted in the transfer of force to the extremities, which can lead to greater limb strength and limb speed (18,23,37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation